A Study on Crowd Detection and Density Analysis for Safety Control - Chaudhari, Mayur D; Ghotkar, Archana S (International Journal of Computer Sciences and Engineering, 2025)
Most of the studies based on tracking individuals, crowd counting, finding the region of motion and crowd detection. Crowd detection and density estimation from crowded images have a wide range of application such as crime detection, congestion, public safety, crowd abnormalities, visual surveillance and urban planning. The purpose of crowd density analysis is to calculate the concentration of the crowd in the videos of observers. Pattern recognition technique helps to estimate the crowd detection count and density by using face and detection. The job of detecting a face in the crowd is complicated due to its variability present in human faces including color, pose, expression, position, orientation, and illumination. The counting performance has been steadily improved because of Deep Convolutional Neural Network.